Remote sensing analysis of base cover of the water in Bontosua Island, Pangkajene and Islands Regency - Nyompa, Achmad Husein; Nurdin, Nurjanna; Haris, Abdul; Faizal, Ahmad; Rani, Chair (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Among the Spermonde Archipelago is strategically important and predominantly medieval islands is Bontosua Island. In order to preserve the health and vitality of the ecosystems, the local communities on this island actively participate in environmental conservation. With the help of this study, the bottom cover of the waters surrounding Bontosua Island, Pangkajene Regency, and the archipelago will be mapped, and the relationships between various types of bottom cover will be ascertained. Methods: From March to September of 2022, the study was carried out. Images from the Sentinel-2A satellite were obtained on July 29, 2021. Using the Lyzenga procedure and the values ki/kj = 0.876875437 and a = -0.280796034, water column adjustment was carried out. The Unsupervised Classification approach was used to classify the images, and the Rapid Reef Assessment (RRA) method was used to verify the bottom water cover in the field. Findings: With a total area of 69.42 hectares, the results revealed seven dominating objects: deep sea, sand, dead coral, dead coral with algae, and coral debris (11.17 ha), living coral (17.32 ha), broken coral (12.73 ha), sand (4.43 ha), seagrass (12.61 ha), and dead coral with algae (11.16 ha). Conclusion: In the waters surrounding Bontosua Island, live coral constituted the greatest portion of the bottom cover, accounting for 25% of the total, while sand made up the least amount, just 6%. Novelty/Originality of this Study: The study on Bontosua Island's water bottom cover is novel due to its use of Sentinel-2A satellite imagery combined with the Lyzenga procedure and Unsupervised Classification approach, offering high-resolution mapping of underwater ecosystems. Additionally, the study's comprehensive classification and verification process through RRA provides detailed insights into the distribution and health of various bottom cover types, contributing to enhanced environmental conservation efforts in the Spermonde Archipelago.